Navigating Academic Success: Exploring the Role of Self-Perceived Coping Strategies Among Preservice Teachers - Haley M Olson; Teddy D Roop; Kelly ONeal-Hixson (The Advocate, 2024)
This study examines self-perceived coping strategies and academic success among preservice teachers in teacher preparation programs. Understanding the self-reported coping strategies preservice teachers utilize in teacher preparation programs is crucial for their preparation and academic performance. By analyzing and discussing self-reported survey data, the research identifies patterns and trends that can inform future practices to support preservice teachers. Findings indicate that preservice teachers self-reported using various coping strategies but predominantly utilized Problem-Solving coping strategies when presented with stressful situations. The study further discusses and provides recommendations for how university-school partnerships can provide the necessary supports for preservice teachers to be fully prepared as professionals.
Keywords: coping strategies; resilience; academic rigor; preservice teachers